If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(x + 2) = -27 Reorder the terms: -9(2 + x) = -27 (2 * -9 + x * -9) = -27 (-18 + -9x) = -27 Solving -18 + -9x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -9x = -27 + 18 Combine like terms: -18 + 18 = 0 0 + -9x = -27 + 18 -9x = -27 + 18 Combine like terms: -27 + 18 = -9 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| 2x+178=90 | | 14m=28 | | -6b+8=5b | | C/9=-3 | | 2x^3+107=21 | | 5/2(x-6)=8 | | W-w+5w=20 | | (6z)/(z^2-16) | | 2x+5.7=6x-3.4 | | 0=x^2+1-25 | | 4(3+4+x)= | | 3000-8x=2000-5x | | 20m-2m+3m-17m-3m=9 | | -2m=-m+14 | | 5/2(x-6)=-27 | | 12+8*2= | | w^2+4w-72=0 | | 10f=3f-28 | | -m+6=3m-2.33333333 | | (7x+5)6=32 | | 4=b/-4 | | 5x^2+5y^2=8 | | -2=-m+14 | | x(3x-4)+2x(x+7)=5x(x-7)+90 | | 3x+2x+1=9 | | 3.5+2x=5 | | -x-3x=17 | | -4b-b+18-6b+-9b=20 | | -43y=-28 | | -7-x+3x=7 | | 89-9+25= | | -2m-m=14 |